Analisis Efektivitas Sistem E-Procurement dalam Pengadaan Barang/ Jasa Pemerintah (Studi pada Fakultas Ilmu Administrasi Universitas Brawijaya) - Suprianto, Agung (Jurnal Ilmiah Administrasi Publik, 2019)
This research was conducted in Faculty of Administrative Sciences Brawijaya University with the aim to know the effectiveness of the procurement of goods and services, through the mechanism of e-procurement system. The results of this study found two findings. First, the process of procurement of goods/ services at the Faculty of Administrative Sciences Brawijaya University is in accordance with the regulations on procurement of government goods/ services, ranging from procedural analysis, related functions, up to the handling of information and documents in the e-procurement system. The research findings also suggest that     a mechanism is needed to control the commitment of the winning bidder companies. Second, the e-procurement system in the procurement of goods/ services at the Faculty of Administrative Sciences Brawijaya University has been effective, although still experiencing the constraints of personnel composition within the Pokja is still dominated by personnel from the Faculty of Administration.